Praecepta, decreta and happiness in Schopenhauer and Seneca: a short comparative study - Bernardes Barbosa Borges, George Felipe (Revista Archai, 2023)
There is an important part in Schopenhauer's bibliography dedicated to reflections on a good life. Between 1826 and 1829, the German philosopher started to think about a eudemonology, an unfinished project, which relied on the rescue of the thought of ancient philosophers. In his discussions there is a great appreciation for Stoic thinking in order to produce a life as little unhappy as possible. Therefore, it seems relevant to revisit Schopenhauer's ideas and compare them with Seneca, who focused on the same topics: the appropriation of the concepts of praecepta and decreta and their connection with happiness.